The Emerging Role of Tissue-Resident Memory CD8+ T Lymphocytes in Human Digestive Tract Cancers - Mei, Xinyu; Li, Huan; Zhou, Xinpeng; Cheng, Min; Cui, Kele (Frontiers in Oncology, 2022)
Malignant digestive tract tumors are a great threat to human public health. In addition to surgery, immunotherapy brings hope for the treatment of these tumors. Tissue-resident memory CD8+ T (Trm) cells are a focus of tumor immunology research and treatment due to their powerful cytotoxic effects, ability to directly kill epithelial-derived tumor cells, and overall impact on maintaining mucosal homeostasis and antitumor function in the digestive tract. They are a group of noncirculating immune cells expressing adhesion and migration molecules such as CD69, CD103, and CD49a that primarily reside on the barrier epithelium of nonlymphoid organs and respond rapidly to both viral and bacterial infection and tumorigenesis. This review highlights new research exploring the role of CD8+ Trm cells in a variety of digestive tract malignant tumors, including esophageal cancer, gastric cancer, colorectal cancer, and hepatocellular carcinoma. A summary of CD8+ Trm cell phenotypes and characteristics, tissue distribution, and antitumor functions in different tumor environments is provided, illustrating how these cells may be used in immunotherapies against digestive tract tumors.